2019
DOI: 10.1055/s-0039-1679932
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Endotracheal Reintubation between Nasal High-Frequency Oscillation and Continuous Positive Airway Pressure in Neonates

Abstract: Objective This study aimed to compare the endotracheal reintubation between nasal high-frequency oscillation (nHFO) and nasal continuous positive airway pressure (nCPAP) with face mask groups who were followed up for up to 7 days. Study Design We performed a retrospective cohort study of extubated neonates admitted between 2013 and 2017. We used a Cox's proportional hazards model to adjust for significant between-group differences in baseline characteristics. Results One hundred and nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…-sentence seems to need some fixing up …], Multifaceted interventions for infection prevention and control and a VAP prevention care bundle must be implemented[you don't 'implement' a care bundle, maybe 'used' or 'pre-prepared and available' or something ] to reduce neonatal VAP. 21,28,29 reviewed and revised the manuscript. All authors approved the final manuscript as submitted and agree to be accountable for all aspects of the work.…”
Section: Discussionmentioning
confidence: 99%
“…-sentence seems to need some fixing up …], Multifaceted interventions for infection prevention and control and a VAP prevention care bundle must be implemented[you don't 'implement' a care bundle, maybe 'used' or 'pre-prepared and available' or something ] to reduce neonatal VAP. 21,28,29 reviewed and revised the manuscript. All authors approved the final manuscript as submitted and agree to be accountable for all aspects of the work.…”
Section: Discussionmentioning
confidence: 99%
“…(table 2) To further verify the results, a summary of all clinical studies referring to NHFOV in newborn infants was made and it was shown in table 4. [35][36][37][38] According to the summary, four reasons were accessible. Firstly, according to the report of Mukerji et al, [39] visible chest oscillation was not necessary because of elimination of CO 2 during NHFOV also occurring in the upper respiratory airway deadspace; Secondly, the mean tidal volume was higher with I:E at 50% than at 33% (2.4 ml vs. 1.4 ml; P < 0.001); [10] Thirdly, the setting of respiratory parameters should also be adjusted according to diagnosis and purpose, and an example was that Luca et al suggested different parameters boundaries for NHFOV use in BPD-risk and postextubation newborn infants.…”
Section: Discussionmentioning
confidence: 99%
“…Studies exploring how NIMV affects the development of BPD when compared to CPAP have shown conflicting results; these disparities are likely related to study design, timing of intervention, and inherent differences in interfaces and devices. How HFNV compares to NIMV is yet to be evaluated, but it appears to be superior to nCPAP in supporting premature infants with improved CO 2 clearance and reducing the need for intubation (106)(107)(108)(109).…”
Section: Discussionmentioning
confidence: 99%
“…Infants in the HFNV group were of lower gestational age and had higher oxygenation indices indicating worse clinical status at recruitment. Despite these differences, HFNV was shown to be as effective as nCPAP in preventing reintubation (108).…”
Section: High Frequency Nasal Ventilation (Hfnv)mentioning
confidence: 98%